The worse survival outcomes reported for melanoma patients having sentinel node biopsy after lymphoscintigraphy the previous day do not appear to be due to overnight migration of Tc99m-nanocolloid tracer. Issue 9 (September 2021) - Chakera, Annette H.; la Cour Sibbesen, Else; Schoedt, Mette; Hölmich, Lisbet R.; Zerahn, Bo; Thompson, John F.
Abstract: Introduction: It has been reported that the survival of patients having sentinel node (SN) biopsy for melanoma the day after lymphoscintigraphy using Tc99m-nanocolloid is worse than that of patients having lymphoscintigraphy and SN biopsy on the same day [1, 2]. A possible explanation suggested is that overnight migration of the tracer from SNs to 2nd-tier nodes occurs, causing failure to remove true SNs. Materials and methods: The possibility of overnight tracer migration leading to errors in SN-identification was investigated in 12 patients scheduled for lymphoscintigraphy the day before surgery by repeating SPECT-CT imaging the next morning, before their SN biopsy. The aim was to check whether onward migration of colloid from previously-identified SNs had occurred. Results: No significant migration of Tc99m-nanocolloid occurred overnight in any patient. All nodes reported to be SNs on day 1 imaging were also present and regarded as SNs on day 2 images. No new foci were visualised on day 2, but some that had been identified on day 1 were not seen on day 2. Conclusions: Since migration of nanocolloid overnight did not occur, this cannot explain the reported survival disadvantage for patients undergoing SN biopsy the day after lymphoscintigraphy. A likely alternative possibility is that inadequate doses of radioisotope were used for next-day procedures, causing the mistaken removal of 2nd-tier nodes instead of true SNs more frequently. Further research is required to explain the reported reduction in survival of patients having next-day SN biopsy procedures, since the possibility has important clinical implications.